1989
DOI: 10.1207/s15328023top1602_9
|View full text |Cite
|
Sign up to set email alerts
|

Item Order Affects Performance on Multiple-Choice Exams

Abstract: to a normal approximation value (2 = -2.795), p < .005.These results were not replicated with the 1961 to 1965 group, the 1976 to 1980 group, and the 1981 to 1985 group.These results indicate that although award recipients in the first 5.-year period were cited more often in textbooks published in 197 1 and 1976, the frequency of citations of con-Note Requests for reprints should be sent to Denis Nissim-Sabat, Department of Psychology, Mary Washington College, Frederickiburg, VA 22401.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 2 publications
0
27
2
Order By: Relevance
“…Sequential order delivers the questions in the order that the content was covered during lectures whereas reverse sequencing does exactly the opposite. In a chapter contiguity exam, the questions are grouped by chapter, but within each chapter-related exam section, the questions are not in chronological order, and the chapter-batches themselves do not have to be inserted consecutively into the exam (Balch, 1989). Questions can also be ordered by increasing or decreasing level of difficulty (Noland, Russell & Madden, 2014;Perlini, Lind & Zumbo, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sequential order delivers the questions in the order that the content was covered during lectures whereas reverse sequencing does exactly the opposite. In a chapter contiguity exam, the questions are grouped by chapter, but within each chapter-related exam section, the questions are not in chronological order, and the chapter-batches themselves do not have to be inserted consecutively into the exam (Balch, 1989). Questions can also be ordered by increasing or decreasing level of difficulty (Noland, Russell & Madden, 2014;Perlini, Lind & Zumbo, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Balch (1989) compared all three approaches to exam construction within a large class of psychology students with the added constraint for the randomly-ordered exam that no two questions from the same chapter could immediately follow one another. His hypothesis was that factual information would be more easily retrieved if accessed in the order that it was first learned and encoded in long-term memory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, such examinations can cause biased measurement results both in favor and disfavor of examinees. As the item orders are different due to variance in forms, this alone could cause students to consider items "harder" or "easier" (Balch, 1989;Impara & Foster, 2006;Laffitte, 1984;Pettijohn & Sacco, 2007). Some reviews of test item order studies have concluded that item order does not influence student test performance (Barcikovski & Olsen, 1975;Carlson & Ostrosky, 1992;Gerov, 1980;Klosner & Gellman, 1973;Tippest & Benson, 1989).…”
mentioning
confidence: 99%
“…However, when research on item order in test forms is reviewed, it is clear that most studies have been based on Classical Test Theory (CTT). Some studies concluded that test item order influences test scores, item parameters, and completion time (Balch, 1989;Picou & Milhomme, 1997).…”
mentioning
confidence: 99%